2020
DOI: 10.1016/j.jhin.2020.07.011
|View full text |Cite
|
Sign up to set email alerts
|

Making medical devices safer: impact of plastic and silicone oil on microbial biofilm formation

Abstract: Background: Medical devices face the challenge of microbial biofilm attached to the surface. Ultimately, this may jeopardize the function of the device and increase the patient's risk of infection. However, reliable methods to prevent biofilm are lacking. Aim: To investigate the effect of silicone oil-coated polypropylene plastic, used in a new automatic urinometer, on biofilm formation; furthermore, to explore the impact of silicone oil viscosity and compare polypropylene with polystyrene, another common medi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 26 publications
1
9
0
Order By: Relevance
“…30 Cellulose promotes delayed bacterial clearance. 31 We found that the majority of E. coli ST1193 and ST131 possessed no curli/no cellulose in this study. This finding was different from a previous study, which might be due to regional disparity.…”
Section: Discussionsupporting
confidence: 49%
“…30 Cellulose promotes delayed bacterial clearance. 31 We found that the majority of E. coli ST1193 and ST131 possessed no curli/no cellulose in this study. This finding was different from a previous study, which might be due to regional disparity.…”
Section: Discussionsupporting
confidence: 49%
“…Based on a dose response titration, 10 µM of CD4-PP was the optimal concentration. In brief, 50 µL of 10 6 CFU/mL of uropathogenic E. coli CFT073 in 150 µL LB broth without salt with or without CD4-PP were added [ 23 ]. After 3 days of incubation at 37 °C, the old media was discarded, and the wells were washed 3 × with sterile water.…”
Section: Methodsmentioning
confidence: 99%
“…PGPR associations with host plants enhance the biosynthesis of defense-related molecules by increasing the level of defense-responsive proteins, which provide survival support under stress conditions. Changes in biochemical and physiological parameters can account for PGPR's ability to induce stress tolerance through osmolyte production [137], antioxidant production [138], ACC deaminase activity [76], phytohormonal content [139], and biofilm formation [140].…”
Section: Mechanistic Overview Of Pgpr-mediated Plant Growth Promotion...mentioning
confidence: 99%